The interplay of external support, learning, and social capital in young farmers' agribusiness sustainability - Syamsiah Siti; Sumardjo; Fatchiya Anna; Haryanto Yoyon; Winarno Kodrad (BIO Web of Conferences)
Global food security and environmental sustainability demand innovative approaches to agribusiness, with young farmers increasingly recognized as key agents of change worldwide. This study investigates the influence of external support, learning levels, and social capital on young farmers' effectiveness and agribusiness sustainability in West Java, Indonesia. This Indonesian case study offers valuable insights into factors influencing young farmers' success and agribusiness sustainability, potentially informing policy interventions in other developing nations facing similar challenges. Data from a survey of 227 young farmers were analyzed using structural equation modelling (SEM) with SmartPLS. Results reveal a strong mediating effect of young farmers' effectiveness on the relationship between external support, learning levels, social capital, and agribusiness sustainability across economic, social, and environmental dimensions. These findings suggest that policies supporting young farmer development and capacity building are crucial for enhancing agribusiness sustainability and contributing to global food security and sustainable development goals (SDGs).